Tinjauan Yuridis Pertanggungjawaban Hukum Bagi Debitur Yang Wanprestasi Atas Perjanjian Hutang Piutang - Fahad; Muhammad Andri; Rini Winarsih (GLOBAL SCIENTS PUBLISHER, 2025)
Human being always wants to be able to live decently and adequately, in order to fulfill life, they often apply for debt to the bank, the condition for a debt is that the debtor must have a guarantee in the form of a Mortgage, if an agreement has been made between the debtor and the creditor, a legal relationship arises in the form of a debt-receivable agreement in which the debtor has the right to return according to what was agreed and vice versa, the creditor also has rights. However, often the development of the debtor commits an act that results in negligence or default so that the efforts that must be made by the creditor are to take action according to company regulations and if this is ignored by the debtor, the creditor should take legal action, namely filing a simple lawsuit to the District Court against the debtor who is in default, the purpose of filing this lawsuit is so that the debtor's responsibility does not impact the creditor's losses and the debtor must submit and comply with the instructions of the contents of the inkracht decision. Against this backdrop, the author of this thesis uses a Statute Approach to obtain information from various aspects regarding the legal issue being addressed. This Statute Approach is conducted by examining all laws and regulations related to the legal issues addressed in this thesis. After discussing the existing issues, it can be concluded that, based on this, creditors must resolve the issue of defaulting debtors in the District Court so that the debtor's liability is subject to the contents of the Condemnatoir decision.